1985
DOI: 10.1366/0003702854249178
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Density Measurements Using Tunable Semiconductor Lasers in a Supersonic Flow

Abstract: Tunable semiconductor lasers were used to probe flow-cooled UF6 molecules in a supersonic nozzle expansion. The number density obtainable and condensation characteristics were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Simultaneous energy and momentum conservation in such collisions can be accommodated by dimer rotation 19. This two‐body encounter theory increases equilibrium dimer populations and formation rates by orders of magnitude compared with a three‐body theory, in agreement with observations 18, 22, 23. It explains why UF 6 /G mixtures experience dimer formation much earlier during supersonic jet expansion in self‐cooling jets than what would be expected on the basis of a three‐body theory.…”
Section: Laser Isotope Separation By Condensation Suppressionsupporting
confidence: 76%
See 1 more Smart Citation
“…Simultaneous energy and momentum conservation in such collisions can be accommodated by dimer rotation 19. This two‐body encounter theory increases equilibrium dimer populations and formation rates by orders of magnitude compared with a three‐body theory, in agreement with observations 18, 22, 23. It explains why UF 6 /G mixtures experience dimer formation much earlier during supersonic jet expansion in self‐cooling jets than what would be expected on the basis of a three‐body theory.…”
Section: Laser Isotope Separation By Condensation Suppressionsupporting
confidence: 76%
“…This was because prevailing theory demanded that three‐body collisions were necessary 20. However, published measurements by Kim et al at Los Alamos22 and by Human in South‐Africa23 showed that the onset of UF 6 dimer formation in supersonic free jets started much sooner during supersonic expansions than expected. The same phenomenon had been observed earlier for supersonic expansions of SF 6 and other gases,18 but dimer formation in supersonic expansions of UF 6 had theretofore been avoided in MLIS experiments to preserve a sharp absorption spectrum 24, 25…”
Section: Laser Isotope Separation By Condensation Suppressionmentioning
confidence: 92%